2011
DOI: 10.1007/s10499-010-9408-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofloc technology (BFT) on the early postlarval stage of pink shrimp Farfantepenaeus paulensis: growth performance, floc composition and salinity stress tolerance

Abstract: Biofloc rearing media provides a potential food source for shrimp reared in limited or zero water exchange systems. This culture system is environmentally friendly as it is based on limited water use and minimal effluent is released into the surrounding environment. In this study, we evaluated the survival, growth performance and salinity stress tolerance of pink shrimp Farfantepenaeus paulensis postlarvae reared from PL 10 to PL 25 in a biofloc technology limited water exchange system. PL (mean ± SD weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 50 publications
3
55
2
9
Order By: Relevance
“…In [46] was observed that presence of bioflocs resulted in increases of 50% in weight and almost 80% in final biomass in F. paulensis early postlarval stage when compared to conventional clear-water system. This trend was observed even when postlarvae were not fed with a commercial feed (biofloc without commercial feed).…”
Section: Applications In Aquaculture 41 Nursery and Grow-outmentioning
confidence: 95%
See 3 more Smart Citations
“…In [46] was observed that presence of bioflocs resulted in increases of 50% in weight and almost 80% in final biomass in F. paulensis early postlarval stage when compared to conventional clear-water system. This trend was observed even when postlarvae were not fed with a commercial feed (biofloc without commercial feed).…”
Section: Applications In Aquaculture 41 Nursery and Grow-outmentioning
confidence: 95%
“…vannamei [44,48], P. monodon [51], F. paulensis [15,46], F. brasiliensis [37,52] and F. setiferus [34]. The primary advantage observed is related to a better nutrition by continuous consumption of biofloc, which might positively influence grow-out performance a posteriori [53], but was not always the case [54].…”
Section: Applications In Aquaculture 41 Nursery and Grow-outmentioning
confidence: 99%
See 2 more Smart Citations
“…Biofloc technology has gained attentions recently as a sustainable and eco-friendly method of aquaculture which controls water quality, along with the production of value added microbial proteinaceous feed for the aquatic organisms. The use of BFT systems in the marine shrimp aquaculture has been extensively studied (Emerenciano et al 2011(Emerenciano et al , 2012b(Emerenciano et al , 2013bRay et al 2011;Xu and Pan 2012;da Silva et al 2013;Schveitzer et al 2013;de Souza et al 2014;Kumar et al 2014). The technology is cost-effective and environment-friendly and supports sustainable aquaculture (Naylor et al 2000;Avnimelech and Kochba 2009 …”
Section: Introductionmentioning
confidence: 99%